Predicting Parental Mental Health During COVID-19: Economic Pressure, COVID-19 Stress, and Coping Strategies - Morgan, Derek Daniel; Higgins, Connað Dael; Ingram, Paul B.; Rogers, Christy Rae (Frontiers in Psychology, 2022)
As the COVID-19 pandemic continues, understanding connections between economic pressures and mental health experiences is critical in comprehending how stressful global events can affect families. Although economic pressures and stress can negatively impact mental health, approach coping strategies may provide reductions in negative mental health experiences for parents compared to avoidant coping strategies. Despite recent work showing that stress resulting from the pandemic can have negative implications for the mental health of parents with young children, there is little known about the mental health of parents with adolescents. This study utilized a longitudinal sample of 198 parents (194 biological parents; 103 Fathers, 91 Mothers) of adolescents and examined the mediating impact of COVID-19 stress on the relationship between economic pressure and subsequent depressive and anxious symptoms. Additionally, approach and avoidant coping strategies were examined as potential moderators between COVID-19 stress and later mental health. Results indicated that parents who experienced economic pressure reported worsening mental health across the school semester, with COVID-19 stress mediating this pathway. Further, approach coping strategies moderated the association between COVID-19 stress and later anxiety symptoms such that higher levels of coping associated with greater rates of later anxiety symptoms, while lower levels of coping associated with less anxiety symptoms later. Avoidant coping strategies also moderated these associations, such that greater use associated with greater depressive and anxious symptomology later. These findings emphasize that parents are experiencing worsening mental health following the onset of the pandemic and that there is an urgent need for increased mental health services to assist families during this time.